2016
DOI: 10.1016/s2213-8587(15)00386-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma urate concentration and risk of coronary heart disease: a Mendelian randomisation analysis

Abstract: SummaryBackgroundIncreased circulating plasma urate concentration is associated with an increased risk of coronary heart disease, but the extent of any causative effect of urate on risk of coronary heart disease is still unclear. In this study, we aimed to clarify any causal role of urate on coronary heart disease risk using Mendelian randomisation analysis.MethodsWe first did a fixed-effects meta-analysis of the observational association of plasma urate and risk of coronary heart disease. We then used a conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 27 publications
4
105
0
5
Order By: Relevance
“…Similar findings have been observed with other mouse crosses [15,23,30]. These findings are consistent with the observation made from Mendelian randomization studies of HDL for role in human coronary heart disease [31,32]. Although Mendelian randomization studies of blood lipids have suggested a role for triglyceride and LDL cholesterol in human coronary heart disease, no significant correlations with atherosclerotic lesions were observed in the present cross or previous crosses [13,33].…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings have been observed with other mouse crosses [15,23,30]. These findings are consistent with the observation made from Mendelian randomization studies of HDL for role in human coronary heart disease [31,32]. Although Mendelian randomization studies of blood lipids have suggested a role for triglyceride and LDL cholesterol in human coronary heart disease, no significant correlations with atherosclerotic lesions were observed in the present cross or previous crosses [13,33].…”
Section: Discussionsupporting
confidence: 93%
“…The method is being increasingly used in practice, with applications including analyses of the causal effects of plasma urate on coronary heart disease risk [10], of height on income [11], of sleep patterns on type 2 diabetes [12], and of pubertal development on prostate cancer risk [13]. However, critical assessment of the method is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…it has a non-zero mean) then a random effects meta-analysis will be biased, but MR-Egger regression [11] can still yield reliable inferences. MR-Egger regression has been used extensively as a sensitivity analysis tool since its proposal for this reason (see [12,13,14,15,16] for some recent examples), although its estimate can often suffer from a lack of precision. In this paper we choose to focus solely on the IVW estimate.…”
Section: Heterogeneity Assessmentmentioning
confidence: 99%